AN ANALYSIS OF THE ECONOMIC IMPACTS OF AIR POLLUTION IN THE URBAN AREAS: BIBLIOGRAPHIC REVIEW - Gaybullaev, Olimjon (Economica, 2024)
Air pollution is a severe problem affecting cities worldwide, with significant environmental and public health implications. Air quality has become challenging as cities grow rapidly with far-reaching socioeconomic consequences. This paper aims to provide a bibliographic review of existing literature on the economic impacts of air pollution in urban areas. The review includes studies that measure health costs, labour productivity impacts, household consumption, stock market performance, and tourism. The findings show that air pollution results in significant economic burdens, such as increased healthcare costs due to pollution-related illnesses and productivity losses. Additionally, it negatively affects household consumption, stock market valuation, and tourism revenue.